Kinetics of aqueous extraction of phenolic compounds from processed yerba mate leaves - López, Gabriela Gisela (2021)
Fil: López, Gabriela Gisela. Universidad Nacional de Misiones. Facultad de Ciencias Exactas, Químicas y Naturales; Argentina.